PERANCANGAN SISTEM INFORMASI M-SCHOOL PADA SMA NEGERI 33 JAKARTA - Jenie Sundari; Muhamad Derajat (Reputasi: Jurnal Rekayasa Perangkat Lunak, 2020)
The process of processing attendance data at the 33 Jakarta High School is done manually by the teacher. Such attendance and assessment processing systems require renewal by utilizing existing technologies in the school environment. The technology that is currently developing rapidly is the reason researchers to develop online attendance information systems. The research aims to develop student attendance information systems online in order to be able to complete the absence of data processing and attendance of the absence of information for parents from the school. So far, parents can only know the attendance and grades of students when taking report cards only. By conducting this research the researcher wants parents to be able to know the student's attendance and grades at any time. The research method used is a waterfall. The first stage is the analysis of device requirements. The second step is application design. The third stage is making program code. The fourth stage is testing applications and benefits to users. The last stage of program maintenance is periodically to avoid any errors that arise. The maintenance process can repeat the development process starting from specification analysis to changes to existing software, but not for making new devices.